2015
DOI: 10.3390/ma8020392
|View full text |Cite
|
Sign up to set email alerts
|

A Miniaturized Antenna with Negative Index Metamaterial Based on Modified SRR and CLS Unit Cell for UWB Microwave Imaging Applications

Abstract: A miniaturized antenna employing a negative index metamaterial with modified split-ring resonator (SRR) and capacitance-loaded strip (CLS) unit cells is presented for Ultra wideband (UWB) microwave imaging applications. Four left-handed (LH) metamaterial (MTM) unit cells are located along one axis of the antenna as the radiating element. Each left-handed metamaterial unit cell combines a modified split-ring resonator (SRR) with a capacitance-loaded strip (CLS) to obtain a design architecture that simultaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
68
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 36 publications
0
68
0
Order By: Relevance
“…Unfortunately, the aforementioned approaches suffer from large sizes, design methodology, complex feeding network and fabrication processes, particularly in the high frequencies. As Pendry investigated the first negative refractive index perfect lens (i.e., double negative MTMs with simultaneously negative permittivity, permeability and negative index of refraction) in 2000 [17], it is possible to design a compact size and high directive antennas [18,19]. Furthermore, metamaterial structures composed of 3-D metal grid superstrates have been used to improve the directivity of the antennas [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the aforementioned approaches suffer from large sizes, design methodology, complex feeding network and fabrication processes, particularly in the high frequencies. As Pendry investigated the first negative refractive index perfect lens (i.e., double negative MTMs with simultaneously negative permittivity, permeability and negative index of refraction) in 2000 [17], it is possible to design a compact size and high directive antennas [18,19]. Furthermore, metamaterial structures composed of 3-D metal grid superstrates have been used to improve the directivity of the antennas [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, these approaches can make the low bandwidth, efficiency, and gain of antenna [8]. Recently, using metamaterial (MTM) in antenna design has been developed for improving antenna parameters and miniaturizing antenna size [9,10]. Nevertheless, the approach method is required the sophisticated structures which can be fabricated costly and time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the approach method is required the sophisticated structures which can be fabricated costly and time consuming. For example, Islam et al reported that a negative index MTM created by combining a modified split-ring resonator (SRR) with a capacitance-loaded strip (CLS) which installed on the radiating patch to obtain the antenna design architecture that simultaneously exhibits both enhanced antenna performance and reduced the antenna size [9]. It was also reported the using of 3D isotropic µ-negative (MNG) MTM loaded on a microstrip circular patch antenna to reduce size and obtain good performance [10].More recently, the use of multi-CSRR resonances etches on ground plane of microstrip antenna for size reduction and gain enhancement [11 -13].…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials are a series of composite materials that can exhibit some special properties. Depend on these properties, we can obtain many applications [1,10,11]. Chiral metamaterials (CMMs) [1,12], which are constructed from artificial sub-wavelength metallic cells, have recently been reported to exhibit strong optical activity.…”
Section: Introductionmentioning
confidence: 99%